Ensuring the protection of historical truth as a new principle of contemporary Russian constitutional law - P. A. Astafichev (Правоприменение, 2021)
The subject of the article is the content of the constitutional amendment of 2020 on the need to ensure the protection of historical truth.The purpose of the research is confirmation or confutation of the hypothesis that protection of historical truth should not be provided by measures of constitutional and legal regulation, since this would conflict with other constitutional principles.The methodology of research includes analysis of academic researches concerning the essence of historical truth, interpretation of Russian Constitution.The main results, scope of application. The author proves that "historical truth" in the constitutional and legal sense is the goal of an objectively and conscientiously minded researcher, guaranteed in a free democratic society by the constitutional right to freedom of thought, scientific creativity and expression. Goal-setting in cognition is a matter of mental activity that is difficult for the democratic control of the state and law. From a normative point of view the moral aspect exists here only (the search for historical truth is a virtue, its distortion is a vice). Constitutional democracy is based on the will and needs of today's generation of people. The past, of course, has a certain significance, but it cannot be considered decisive. An excessive preoccupation with traditions and the historical past is fraught with stagnation, stagnation or even degradation of the state mechanism. Constitutional regulation of historical truth leads to unnecessary sacralization of the history of the state, which is profoundly alien to the true legal essence of the constitutional system of a modern democratic society and the objectivity of historical and legal science. State-legal influence in this area is difficult and entails risks of legally binding ideology, which is prohibited by the first chapter of the "Fundamentals of the constitutional order" of the Constitution of the Russian Federation (part 2 of article 13) and the current acts of the Russian Constitutional Court.Conclusions. The legal obligation to "ensure the protection of historical truth" deserves a critical assessment, since it is difficult to combine with the constitutional rights to freedom of scientific creativity, freedom of thought and speech, the principle of ideological diversity and the democratic nature of the Russian state. The right of citizens to their own position on historical issues and search for their "historical truth" followed from the constitutional regulation before the constitutional amendments of 2020 and continues to operate today due to the immutability of chapters 1, 2 and 9 of the Constitution of the Russian Federation.